Delhi Transport Department : case of Uber taxi rape - Raghuram, G., 1955- (SAGE Knowledge. Cases., 2017)
This case describes the events following an incident of a rape in a taxi associated with Uber, by its driver. Uber was an application based taxi operator. The events raised several issues for government systems and processes, such as need for regulation of new formats of business like application based taxi services, integrated databases, checks against forgery and holistic approach towards women safety. The case also brings out how an e-commerce business raises regulatory concerns.